Total synthesis, structure elucidation and expanded bioactivity of icosalide A: effect of lipophilicity and ester to amide substitution on its bioactivity - Dangi, Abha; Pande, Bharat; Agrawal, Sonia; Sarkar, Dhiman; Vamkudoth, Koteswara Rao; Marelli, Udaya Kiran (Organic & Biomolecular Chemistry, 2023)
The first total synthesis of icosalide A, an antibacterial depsipeptide that is unique in that it contains two lipophilic beta-hydroxy acids, has been achieved by following Fmoc solid-phase peptide synthesis in combination with solution-phase synthesis. The ambiguity in the absolute stereochemistry of icosalide A has been resolved by synthesizing the reported structures and other relevant diastereomers of icosalides and comparing their NMR data. NMR-based structure elucidation of icosalide A revealed a well-folded structure with cross-strand hydrogen bonds similar to the anti-parallel beta-sheet conformation in peptides and displayed a synergistic juxtaposition of the aliphatic sidechains. 12 analogues of icosalide A were synthesized by varying the constituent lipophilic beta-hydroxy acid residues, and their biological activities against Bacillus thuringiensis and Paenibacillus dendritiformis were explored. Most of these icosalide analogues showed an MIC of 12.5 & mu;g mL(-1) against both bacteria. Swarming inhibition by icosalides was least in B. thuringiensis (8.3%) compared to that in P. dendritiformis (33%). Furthermore, this is the first report of icosalides showing assured inhibitory action (MIC between 2 and 10 & mu;g mL(-1)) against the active stage of Mycobacterium tuberculosis and cancer cell lines such as HeLa and ThP1. This study could help optimize icosalides for anti-TB, antibacterial, and anti-cancer activities.

Understanding the antimicrobial and antioxidant potential of bioinspired platinum nanoparticles synthesized using ocimum tenuiflorum - Varma, Sanjana; Bamb, Aagam Lalit; Tambe, Sayali A.; Burade, Dimpal K.; Jagdale, Swati; Pande, Bharat; Vamkudoth, Koteswara Rao; Chaudhari, Bhushan P. (BioNanoScience, 2025)
The emergence of infectious diseases has highlighted the need for novel and effective antimicrobial agents. Platinum nanoparticles (PtNPs) could act as a potent antimicrobial agent due to their unique physicochemical properties. However, the chemical or physical synthesis methods of PtNPs have drawbacks, like irregular shape and use of toxic chemicals. These drawbacks can be effectively overcome by using the biological method synthesis. Thus, this study presents the green synthesis of platinum nanoparticles (PtNPs) using Ocimum tenuiflorum leaf extract as a bio-reductant. The study also comprehensively encompasses the role of multiple process parameters for the green synthesis of PtNPs. The high-resolution transmission electron microscopy (HR-TEM) revealed spherical PtNPs with an average size of 2.36 ± 0.5 nm that exhibits excellent stability (zeta potential, −45.67 ± 2.57 mV). Phytochemical analysis of aqueous O. tenuiflorum leaf extract was performed to assess the bioactive compounds like saponins, phenols, and tannins, reducing sugars and flavonoids. The PtNPs demonstrated significant antioxidant activity of 86.9 ± 0.12% at 10 µg/mL. Further, the biosynthesized PtNPs showed efficient antimicrobial activity with a minimum inhibitory concentration (MIC) of 6.25 µg/mL against Escherichia coli and 1.5 µg/mL against Staphylococcus aureus. These findings highlight the therapeutic potential of eco-friendly PtNPs for pharmaceutical and biotechnological applications.